Establishing a Nexus Between Residential Quality and Health Risk: An Exploratory Analytical Approach. Issue 6 (December 2013) - Aliu, I. R.; Adebayo, A.
One of the basic sources of risk to public health is the built environment. Both housing and health are social issues that need to be constantly ensured by urban stakeholders. There seems to be a strong connection between housing quality and health conditions of inhabitants. However, not much is known about the health risks that poor housing conditions could pose to the residents in Lagos, Nigeria. This paper therefore examines the impacts of housing conditions on the health of dwellers in Lagos metropolitan areas. Data were obtained from survey of residences in three areas of Lagos. Bivariate and multivariate analyses showed that there are strong negative correlations between housing conditions and health of residents and the residential use value, space quality and structural quality factors are responsible for health risk experienced in the areas under study.